RECORDS OF POST-CRETACEOUS-TERTIARY BOUNDARY MILLENNIAL-SCALE COOLING FROM THE WESTERN TETHYS: A SMOKING GUN FOR THE IMPACT-WINTER HYPOTHESIS? - Galeotti S.; Brinkhuis H.; Huber M. (My University, 2004)
The record of both dinoflagellate cysts and benthic foraminifera across the Cretaceous-Tertiary boundary at El Kef, Tunisia, reveals a brief expansion of the Boreal bioprovince into the western Tethys, suggesting that an ∼2 k.y. cooling occurred during the earliest Danian. We show that this prolonged cooling phase is consistent with the oceanographic response to an impact winter.
Keywords: Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая